Lean Government Concept and Design Over Service Administration in Indonesian ID Card - Apiet Ginanjar; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2019)
Bureaucracy in Indonesia have problematic in public services performance due to lack of apparatus resources quality. Here, the solution to solve the problem cannot fixed. By using the lean thinking concept, we can improve this problem to fix it. This concept namely lean government to find best solution whether the application of Lean Government concept with Lean Consumption Map (LCM) and DMAIC (Define, Measure, Analyze, Improve, Control). This method can be applied in public services, especially in the Indonesian ID Card service process over Department of Population and Civil Registration of South Tangerang, West Java, Indonesia. In this study, we use qualitative research methods to obtained the data based on survey, observations, interview, analysis of documents and records or reports from Department of Population and Civil Registration, South Tangerang, West Java, Indonesia. The result showed, Value to Waste Ratio increased from 9.1% to 43% while in the provider side from 7.2% to 46%. This study shows that the Lean thinking methodology can be embraced by public services to create an efficient and effective process in reducing the service process time.